Evaluación financiera de las cuentas por cobrar del Cuerpo de Bomberos Municipal de Puebloviejo del periodo 2021 -2022. - Ortiz Moreira, Wilson Alejandro (2024)
This case study focused on the Financial Evaluation of the Accounts Receivable of the Municipal Fire Department of Puebloviejo for the Period 2021 -2022 where it was possible to detect if anomalies were occurring within them that could put the stability of the entity at risk. , since accounts receivable are essential in every company. However, due to the lack of adequate management and the lack of effective credit and collection policies, accounts receivable increased, which in turn led to a decrease in liquidity in the accounts and in solvency, due to maintaining a adequate financial stability. It is extremely important to take into consideration that this case study was carried out through a qualitative and quantitative approach, where financial indicators were used to help us measure the profitability of the aforementioned institution using an interview as a tool for the data collection that helped us with the execution of this project.